Reliability and factor analysis of children′s fear survey schedule-dental subscale in Indian subjects - Singh P; Pandey R; Nagar A; Dutt K (Wolters Kluwer Medknow Publications, 2010)
Context: Fear to visit a dentist is a common observation even in adults; however, among children it becomes one of the most important issues for a dentist. Psychographic analysis of the factors that add to fear level of the children can be accessed through Children fear survey schedule-dental subscale (CFSS-DS); however, its varied applicability in different environmental situations has been tested through this paper. Aims: The aim of present study is to evaluate the reliability and factor structure of the Indian version of the CFSS-DS. Materials and Methods: The routine patients attending Outpatient Department of Pedodontics with Preventive Dentistry, Faculty of Dental Sciences, Lucknow, India (n=197, aged 7-12 years old) were evaluated for children′s fear survey schedule-dental subscale which was filled by parents on behalf of the child. Statistical Analysis: Reliability analysis (alpha) was performed to assess the internal consistency of the Indian translation of the scale. Factor analysis (principle components, varimax rotation) was employed to assess the factor structure. Results: Children fear survey scale-dental subscale was found to be equally reliable (Cronbach alpha = 0.92) and applicable among Indian subjects. However, factorization revealed emergence of 1) hospital, injections and hospital personnel, 2) drilling and interaction with unknown, 3) dental care personnel and practices. Conclusion: The present study extended the universal applicability of children fear survey schedule -dental subscale, while at the same time it was able to highlight different facets of problem in different environments.